Silent Neighbor (A Chloe Fine Psychological Suspense Mystery-Book 4) - Blake, Pierce (Lukeman Literary, 2019)
"A masterpiece of thriller and mystery. Blake Pierce did a magnificent job developing characters with a psychological side so well described that we feel inside their minds, follow their fears and cheer for their success. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) SILENT NEIGHBOR (A Chloe Fine Mystery) is book #4 in a new psychological suspense series by bestselling author Blake Pierce, whose #1 bestseller Once Gone (Book #1) (a free download) has over 1,000 five-star reviews. When a flashy, new neighbor flaunts her wealth in a suburban town, it isn't long before she's found murdered. Did her flaunting ways upset her envious neighbors? Or was there a deeper secret to her husband's fortune? FBI VICAP Special Agent Chloe Fine, 27, finds herself immersed in a small-town world of lies, cliques, gossip and betrayal as she tries to separate truth from lies. But what is the real truth? And can she solve it while also dealing with the release of her troubled father from jail, and the spiraling down of her troubled sister? An emotionally wrought psychological suspense with layered characters, small-town ambiance and heart-pounding suspense, THE SILENT NEIGHBOR is book #4 in a riveting new series that will leave you turning pages late into the night. Book #5 in the CHLOE FINE series will be available soon.
Keywords: Dobrodružství, napětí, thrillery; Krimi, detektivky